Exposure to human immunodeficiency virus/hepatitis C virus in hepatic and stellate cell lines reveals cooperative profibrotic transcriptional activation between viruses and cell types. Issue 6 (5th October 2016) - Salloum, Shadi; Holmes, Jacinta A.; Jindal, Rohit; Bale, Shyam S.; Brisac, Cynthia; Alatrakchi, Nadia; Lidofsky, Anna; Kruger, Annie J.; Fusco, Dahlene N.; Luther, Jay; Schaefer, Esperance A.; Lin, Wenyu; et al.
Abstract : Human immunodeficiency virus (HIV)/hepatitis C virus (HCV) coinfection accelerates progressive liver fibrosis; however, the mechanisms remain poorly understood. HCV and HIV independently induce profibrogenic markers transforming growth factor beta‐1 (TGFβ1) (mediated by reactive oxygen species [ROS]) and nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NFκB) in hepatocytes and hepatic stellate cells in monoculture; however, they do not account for cellular crosstalk that naturally occurs. We created an in vitro coculture model and investigated the contributions of HIV and HCV to hepatic fibrogenesis. Green fluorescent protein reporter cell lines driven by functional ROS (antioxidant response elements), NFκB, and mothers against decapentaplegic homolog 3 (SMAD3) promoters were created in Huh7.5.1 and LX2 cells, using a transwell to generate cocultures. Reporter cell lines were exposed to HIV, HCV, or HIV/HCV. Activation of the 3 pathways was measured and compared according to infection status. Extracellular matrix products (collagen type 1 alpha 1 (CoL1A1) and tissue inhibitor of metalloproteinase 1 (TIMP1)) were also measured. Both HCV and HIV independently activated TGFβ1 signaling through ROS (antioxidant response elements), NFκB, and SMAD3 in both cell lines in coculture. Activation of these profibrotic pathways was additive following HIV/HCV coexposure. This was confirmed when examining CoL1A1 and TIMP1, where messenger RNA and protein levels were significantly higher in LX2 cells in coculture following HIV/HCV coexposure compared with either virus alone. In addition, expression of these profibrotic genes was significantly higher in the coculture model compared to either cell type in monoculture, suggesting an interaction and feedback mechanism between Huh7.5.1 and LX2 cells. Conclusion: HIV accentuates an HCV‐driven profibrogenic program in hepatocyte and hepatic stellate cell lines through ROS, NFκB, and TGFβ1 up‐regulation; coculture of hepatocyte and hepatic stellate cell lines significantly increased expression of CoL1A1 and TIMP1; and our novel coculture reporter cell model represents an efficient and more authentic system for studying transcriptional fibrosis responses and may provide important insights into hepatic fibrosis. (Hepatology 2016;64:1951‐1968).